Respuesta :
Answer:
x=i√14,−i√14,−3+2i,−3−2i
Step-by-step explanation:
Set the function equal to 0 and solve for x.
Answer:
The zeros of given polynomial function [tex]f(x)=(x^2+6x+8)(x^2+6x+13)[/tex] are -4 , -2 [tex]-3+2i,-3-2i[/tex]
Step-by-step explanation:
Given polynomial, [tex]f(x)=(x^2+6x+8)(x^2+6x+13)[/tex]
We have to find the zeros of the polynomial.
Consider the given polynomial, [tex]f(x)=(x^2+6x+8)(x^2+6x+13)[/tex]
Zeros are the point where the value of function is equal to 0 that is
[tex]f(x)=(x^2+6x+8)(x^2+6x+13)=0[/tex]
Using , zero product property , [tex]a.b=0 \Rightarrow a=0 \ or\ b=0[/tex]
we have,
[tex]f(x)=(x^2+6x+8)=0[/tex] or [tex]f(x)=(x^2+6x+13)=0[/tex]
We solve it one by one,
consider [tex]f(x)=(x^2+6x+8)=0[/tex]
we solve the quadratic using middle term splitting method,
6x can be written as 4x + 2x ,
[tex]x^2+4x+2x+8=0[/tex]
taking x common from first two term and 2 common from last two terms, we have,
[tex]\Rightarrow x(x+4)+2(x+4)=0[/tex]
[tex]\Rightarrow (x+4)(x+2)=0[/tex]
Again using zero product rule, we have,
[tex]\Rightarrow (x+4)=0[/tex] or [tex]\Rightarrow (x+2)=0[/tex]
[tex]\Rightarrow x=-4[/tex] or [tex]\Rightarrow x=-2[/tex]
Now, consider the second quadratic equation [tex]f(x)=(x^2+6x+13)=0[/tex]
[tex]\mathrm{For\:a\:quadratic\:equation\:of\:the\:form\:}ax^2+bx+c=0\mathrm{\:the\:solutions\:are\:}[/tex]
[tex]x_{1,\:2}=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
[tex]\mathrm{For\:}\quad a=1,\:b=6,\:c=13:\quad x_{1,\:2}=\frac{-6\pm \sqrt{6^2-4\cdot \:1\cdot \:13}}{2\cdot \:1}[/tex]
[tex]x=-3+2i,\:x=-3-2i[/tex]
Thus, the zeros of given polynomial function [tex]f(x)=(x^2+6x+8)(x^2+6x+13)[/tex] are -4 , -2 [tex]-3+2i,-3-2i[/tex]